Increased Corticosterone Levels due to Chronic Stress Reduces IGF-II Expression in Rattus norvigecus - Ade Septiari Rahman; Reny I’tishom; Ashon Sa’adi (Institute of Medico-legal Publications Pvt Ltd, 2021)
The optimal folliculogenesis process describes a good condition of the female reproductive system.One of the main growth factors in the folliculogenesis is IGF-II which is important for proliferation anddifferentiation of granulosa cells and also steroidogenesis. Chronic stress can cause ovulation failure andfolliculogenesis disorders. Increased corticosterone levels due to chronic stress will cause disruption in the